NEXT-GENERATION DUAL-BORE CANNULA FOR INJECTION OF VITAL DYES AND HEAVY LIQUIDS DURING PARS PLANA VITRECTOMY. Issue 3 (March 2016) - Toygar, Okan; Berrocal, Maria H.; Charles, Martin; Riemann, Christopher D.
Abstract : Purpose: The objective of this study was to introduce and validate a next-generation dual bore cannula for microincisional vitrectomy surgery. Methods: The SideFlō cannula with a closed tip and four vent ports on the sides was designed and manufactured. The cannula is designed to inject vital dyes for macular staining and perfluorocarbon liquids. Injection and venting properties were assessed subjectively in vivo, and venting was quantified in a plastic eye model system; 23-, 25-, and 27-gauge SideFlō cannulas were assessed and compared with existing axial dual bore cannula designs. Results: The SideFlō cannula created a broad fan-like egress of fluid that was perpendicular to the axial direction of the cannula and eliminated the possibility for retinal fluid jet damage. Enhanced outflow venting was clinically relevant in terms of smoother injection experience and less intraocular pressure rise when compared with previous dual bore designs. Testing in a model eye system confirmed marked improvement in passive outflow compared with the first-generation dual bore cannula single vent port design for all gauges. Conclusion: The SideFlō cannula represents a novel next-generation dual bore cannula design with significantly improved performance over first-generation dual bore cannulas. Axial jet damage from fluid injection is eliminated, and pressure equilibration by passive venting from the eye is significantly enhanced. Abstract : A next-generation dual bore cannula for intravitreal administration of dyes and heavy liquids is described. A new tip configuration prevents retinal damage from fluid jet effect, and optimized vent port geometry greatly enhances passive fluid venting.